INFLUENCE OF DRIP IRRIGATION AND NITROGEN FERTIGATION ON YIELD AND WATER PRODUCTIVITY OF GUAVA - SHARMA, SUMAN; KR. PATRA, SANMAY; GOKUL B. ROY; BERA, SOUMEN (The Bioscan, 2013)
A field experiment was carried out during 2009-2010 to 2011- 2012 at the Gangetic alluvial soils of West Bengal, India to assess four irrigation schedules (surface irrigation at IW/CPE 1.0, drip irrigation at 60%, 80% and 100% of crop evapotranspiration) and three nitrogen fertigation levels (80%, 100% and 120% of recommended dose of N) on the yield and water productivity of guava (cv. Psidium guajava L). The results showed that fruit yield of guava increased consistently and significantly with increasing ETc and nitrogen fertilization. However, the highest fruit yield of 18.7 t/ha was obtained with drip irrigation at 100% ETc, whereas the lowest yield of 11.0 t/ha was recorded under drip irrigation at 60% ETc. Similarly, maximum fruit yield of 16.9 t/ha was registered at 100% of recommended dose of N. The interaction between irrigation schedules and N fertigation levels revealed that maximum fruit yield of 21.6 t/ha and water productivity of 17.8 kg/ha-mm was demonstrated under drip irrigation at 100% ETc with 120% of recommended dose of N. Alternatively, surface irrigation scheduled at IW/ CPE 1.0 could also be used advantageously if the initial investment for laying the drip irrigation system is likely to be an impediment to the resource poor farmers for guava cultivation.